A comprehensive study on frictional dependence and predictive accuracy of viscoelastic model for optical glass using compression creep test. Issue 11 (20th May 2019) - Yu, Jianwu; Luo, Hong; Zhang, Yingying; Nguyen, Thai V.; Jiang, Xiaomo; Hu, Junzhi
Abstract: Compression creep tests (CCTs) have been widely used in phenomenological characterization of viscoelastic materials such as glasses. However, disturbed by specimen‐tool interface friction, the real stress‐strain data regarding the pure viscoelastic deformation are frequently misestimated in conventional CCTs, causing decreased accuracies of the derived viscoelastic parameters. This study proposes a comprehensive CCT‐based approach to develop a viscoelastic model with weakened frictional disturbance and enhanced predictive accuracy. An integrated calculation procedure is first built to mathematically characterize the frictional and viscoelastic behaviors of glass during compression. Uniaxial CCTs of a typical borosilicate glass (L‐BAL42) are then performed at varied frictional conditions. The quantified coefficients of interface friction indicate that a minor frictional disturbance is achieved when Nickel foils are used as interfacial layers, whereby a more realistic viscoelastic constitutive relation of the glass is derived. The obtained frictional and viscoelastic constants are further incorporated into computational modeling of the CCT and precision molding processes. The demonstrated consistencies between the simulated and measured results (creep displacement and molding force) suggest that, by technically slashing the interface friction and theoretically correcting the friction‐involved stress in CCTs, the frictional disturbance to experimental stress‐strain data can be effectively weakened, and a viscoelastic model of enhanced predictive accuracy can be thus developed. Abstract : A comprehensive approach is proposed to address the interfacial friction issue in high‐temperature compression creep tests of glass. By using friction‐reducing interlayers and correcting the frictional‐involved stress, the frictional disturbance to experimental stress‐strain data is effectively weakened, and a viscoelastic model of enhance predictive accuracy is thus obtained. Image Credit: Jianwu Yu, Hong Luo, and Yingying Zhang et al.